A comparison of group contingencies on academic compliance. Issue 1 (19th September 2018) - Deshais, Meghan A.; Fisher, Alyssa B.; Kahng, SungWoo
Abstract : We used a reversal design with an embedded multielement design to compare the effects of an independent group contingency and a randomized dependent group contingency on compliance with assigned literacy worksheets in a first‐grade general education classroom. Nine participants were selected based on low levels of compliance in baseline or by teacher identification. Results indicated that both group contingencies increased compliance relative to baseline for the majority of participants. The independent condition produced higher levels of compliance for four students and the randomized dependent condition produced higher levels of compliance for one student. For four students, the two group contingencies were equally effective. A preference assessment indicated that the majority of target students preferred the randomized dependent condition and the majority of nontarget students preferred the independent condition. A number of potential explanations for our preference findings, including the possible role of obtained reinforcement, are discussed.